Keterbatasan Sarana dan Prasarana serta Implikasinya terhadap Minat Belajar Siswa Sekolah Dasar - Asmaalhusna Asmaalhusna; Tabroni Tabroni; Ahmad Sayuti Nainggolan (EduInovasi: Journal of Basic Educational Studies, 2026)
This study aims to determine the limitations of facilities and infrastructure in supporting student learning interest at SDN 36/VI Rantau Panjang. This study used a qualitative case study approach. Data collection techniques were conducted through observation, interviews, questionnaires, and documentation, while data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results indicate that the condition of facilities and infrastructure at SDN 36/VI Rantau Panjang is still relatively limited. These limitations include learning resources such as textbooks, learning media in the form of teaching aids and projectors, as well as supporting infrastructure such as toilets and supporting rooms that still require repair and additions. Despite this, the learning process continues to be carried out as intended. Supporting factors in addressing limited facilities and infrastructure include school support, teachers' creativity in managing learning, and students' internal motivation. Inhibiting factors include limited learning media and inadequate infrastructure. The school's efforts to address these limitations include encouraging teacher creativity and innovation in the use of appropriate learning methods and gradually procuring facilities and infrastructure. These efforts demonstrate the school's commitment to creating a better learning environment to foster student interest in learning.